Ontologi Sains dalam Perspektif Barat dan Islam: (Analisis Filosofis atas Persamaan dan Perbedaannya) - Pajar Tryadi; Salahuddin Harahap (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Ontology is the philosophical foundation that determines the way reality is understood in the development of science. Differences in ontological assumptions will have implications for the way science is constructed, developed, and interpreted. This article aims to philosophically analyze the ontology of science in Western and Islamic perspectives by highlighting its fundamental similarities and differences. This study uses a qualitative approach based on literature studies with descriptive-analytical and comparative methods. The results show that the ontology of Western science tends to emphasize empirical and rational reality as the main object of science, while the ontology of Islamic science is based on the principle of monotheism which looks at reality holistically, including physical and metaphysical dimensions. Although paradigmatically different, the two perspectives have a common point in the recognition of the order of nature and the role of reason in understanding reality. This article affirms the importance of ontological dialogue between the West and Islam in formulating a scientific paradigm that is not only technically advanced, but also philosophically and ethically meaningful.